Značennâ civìlìstičnoї doktrini dlâ rozbitku ûridičnogo fakul’tetu L’vìvs’kogo unìversetu (počatok XVII-kìnec’ XIX stolìttâ) - Kahnič, Volodimir (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The article proves the importance of civil doctrine for the functioning of the Law Faculty at Lviv University since the time of its foundation. There were few specialists in Galicia who could perform their tasks properly and so the study of the principles of civil law was recognized as necessary. These important tasks were not always well performed, because of poor skills of government officials. The necessity to teach the magistracy and train their skills for performing state tasks arose. However, forming a civics school in Lviv was not an easy task.Galicia had been a part of various states during different historical periods. Those periods had great impact on establishing civil law doctrine, in other words, those fundamentals that became the basis of civil law specialists’ views.When Lviv university was founded in 1661, a group of like-minded persons was formed. They considered that it was not possible to build a powerful state, strengthen etatist ideals, assure the development of education and the university without proper study of civil law and its fundamentals.The fundamentals of civics date back to ancient Roman Empire. It was Roman Empire where civics was used for the first time not only theoretically but also using civil standards in real-life situation. At the university there were no considerable changes in the teaching process compared to that in the Jesuit Collegium. Awarding academy status was mainly a political decision.Alterations took place only when functioning of the law faculty in Lviv was re-establishedby the Austrian emperor Joseph II in 1784. Syllabi of Law Faculty at Lviv University during its Austrian period enclosed main fields of juridical science of that time, mainly: History of State System, History of Austrian and German Law, Roman Law, German Law, Canon Law, Administrative System, Austrian Civil Procedure, Austrian Criminal Law, European Philosophy of Law, European International Law, Commercial and Exchange Law, Forensic Medicine, Financial Law, Economics, National Law of Constitutional Monarchies, Austrian Common Financial Laws, Austrian Political Law, Austrian Mining Law, State Accounts, Austrian Common Private Law, European Statistics.Famous professors such as Anton Pfleger von Wertenau, Jan Ambros Edler von Rechtenberg, Dominik Seyfried von Kofil, or Baltazar Borzaga, were offered positions at the Law Faculty of Lviv University. Baltazar Borzaga was the first to head the Civil Law Department at that time called Civil, Pandect and Criminal Law Department. They had to facilitate educational and scientific activities and ensure the teaching of Absolute, International, Roman, Criminal and Canon Law. In 1784, 26 students studied at the law faculty and in 1790 there were already 78 students.The article also demonstrates that the basic requirement of the Austrian authorities towards the Law Faculty of Lviv University was training specialists: lawyers, judges, prosecutors, counsels at law, notaries for Galicia and Lodomeria.
Keywords: civil doctrine; magistracy; Law Faculty; Lviv University; Galicia